IMPLEMENTASI PROGRAM KAMPUS MENGAJAR UNTUK MENINGKATKAN LITERASI, NUMERASI, DAN KARAKTER SISWA DI SEKOLAH DASAR ISLAM TERPADU AL-MINHAJ BANJARWANGI, KABUPATEN GARUT - Elis Badriah; Dendy Syaiful Akbar; Benny Prawiranegara; Farina Nugrahani; Yoga Taufik Hidayat; Feby Filga Cantika; Sidki Rijalul Muwahid; Yuni Anggraeni; Sonia Sonia; Melani Safitri (Universitas Mataram, 2026)
The Kampus Mengajar Program is an initiative of the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) aimed at improving literacy, numeracy, and character development among elementary school students, particularly in disadvantaged, frontier, and outermost (3T) regions. This program was implemented at SD IT Al-Minhaj Banjarwangi, Garut Regency, involving collaboration between university students, field supervisors, and school teachers. The implementation methods included participatory, contextual, collaborative, and project-based approaches through the provision of creative learning media, literacy and numeracy assistance, and the habituation of positive behaviors. The results show an increase in learning motivation, student engagement, and comprehension in literacy and numeracy. Furthermore, multi-stakeholder collaboration strengthened the learning environment and encouraged the sustainability of learning innovations at the school. Challenges such as limited infrastructure were addressed through creative strategies and continuous support from various stakeholders. The program proved to be effective and can be replicated in schools with similar conditions.